A Further Empirical Investigation of the Dividend Adjustment Process - WU, Chunchi (Institutional Knowledge at Singapore Management University, 1987)
This paper analyzes the dividend adjustment process in the presence of cost of adjustment and information uncertainty. It proposes an integrated model consistent with the practical decision process to characterize the dividend adjustment process. It is analytically demonstrated that the residual theory, partial adjustment and adaptive expectations models are all special cases of the integrated model specified in this paper. Marquardt's non-linear regression method is adopted to estimate the parameters of the integrated model, using both quarterly and annual data of earnings and dividends from a randomly selected sample. Empirical results show that the integrated model better explains the firm's dividend decision process.